Polycentric spatial development: Institutional challenges - Amy Rader Olsson; Göran Cars (European Regional Science Association (ERSA), 2010)
Most metropolitan regions advocate cooperation among municipalities and bewteen public and private actors to plan and fund new housing and transportation infrastructure. Just as many experience frustration that such cooperative structures fail to materialize or prove ineffective. A recent study of several municipalities north of Stockholm, Sweden investigated what hinders and opportunities may exist to improve the potential for cooperation and collective action in infrastructure provision. This included a special focus on the challenges of polycentric spatial development that presents a classic social dilemma with uneven payoffs and costs for individual communities. The study includes three cases focused on retail centres, transportation corridors and new housing.
Keywords: 330